Efforts to Improve Adolescent Girls' Knowledge About Dysmenorrhea Through Health Promotion - Carolin, Bunga Tiara; Aulya, Yenny; Fatiha , Salysia Manif; Kirana, Farida Rahmah (Rajaki of Tulip Medika Publisher, 2025)
Menstrual cycles vary greatly from person to person or individual. One of the most common menstrual problems complained of is dysmenorrhea. Dysmenorrhea is pain and cramps in the lower abdomen experienced by women before or during the menstrual cycle. This condition is considered normal if it causes mild symptoms. However, in some cases, dysmenorrhea can cause discomfort to the point of disrupting daily activities. The purpose of this service is to increase the knowledge of adolescent girls about dysmenorrhea through health promotion. The counseling participants are adolescent girls. The service method is by means of lectures and evaluation is carried out by means of direct questions and answers to participants. It is hoped that with increased knowledge about dysmenorrhea, adolescent girls will be able to overcome dysmenorrhea so that it does not interfere with their activities at school.